Domains and Methods of Medical Device Technology Evaluation: A Systematic Review - Fotini Santos Toscas; Daiana Laurenci Orth Blas; Leidy Anne Alves Teixeira; Marisa da Silva Santos; Eduardo Mario Dias (Frontiers Media S.A., 2024)
ObjectivesIdentify, through a systematic review, the main domains and methods to support health technology assessment of Medical Devices (MD) from the perspective of technological incorporation into healthcare systems.MethodsPerformed structured searches in MEDLINE, Embase, BVS, Cochrane Library, and Web of Science for full studies published between 2017 and May 2023. Selection, extraction, and quality assessment were performed by two blinded reviewers, and discrepancies were resolved by a third reviewer.ResultsA total of 5,790 studies were retrieved, of which 41 were included. We grouped the identified criteria into eight domains for the evaluations.ConclusionOverall, studies discuss the need to establish specific methods for conducting HTA in MD. Due to the wide diversity of MD types, a single methodological guideline may not encompass all the specificities and intrinsic characteristics of the plurality of MD. Studies suggest using clustering criteria through technological characterization as a strategy to make the process as standardized as possible.